Orthotypography to improve the writing of gastronomic and academic texts translated into spanish - Usquiano Piscoya, María Magdalena (2021)
This study corresponds to a mixed research perspective, of a propositional type, with the purpose of improving the writing of gastronomic texts in Spanish in students of the curricular experience Direct Translation I of the Universidad César Vallejo, developing aspects that favour the adequate use of the grammatical rules of Spanish and the punctuation marks in the translation of specialized texts. In recent years, a great interest has emerged in research on orthography in relation to translation (Martínez de Sousa, 2004; Veloso, 2004; Claros, 2008). In the theoretical foundation the principles of orthography established by Meneses (2016), the contributions that have referred to communication and the adaptation of uses according to the characteristics of the sender and the client in the translation process are addressed; as well as the orthographic regulations in Spanish. In order to achieve the objectives in this research, a pre-test was created and validated by experts prior to its application. This instrument allowed data collection, its analysis and the discussion of the results. After that, the proposal for the orthographic program in question was designed, accompanied by the corresponding syllabus. Finally, the conclusions and recommendations were established.